The Effectiveness of the Equality Dynamic Learning Model in Increasing Disability Awareness of Students in Inclusion Classes - Sani, Yulvia; Wardany, Ossy Firstanti; Vernanda, Genesa; Herlina, Heni (The Center for Disability Studies and Services Brawijaya University, 2020)
The background of research is low acceptance problem of the presence of students with disabilities caused by the lack of disability awareness in every student that arises due to low social contact. The lack of acceptance can be seen from the reactions of other students when learning. The problem will be very clear when there is of work groups learning, it is very rarely condition, there are other students who immediately propose themselves in one group with him. In addition, there is lacking of support for